2011
DOI: 10.1136/bjsm.2010.081554.40
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma for chronic achilles tendinopathy: a double-blind randomised controlled trial with one year follow-up

Abstract: Introduction Chronic Achilles tendinopathy occurs frequently and is very hard to treat. The disease involves local degeneration of tendon tissue, of which regeneration may be improved by injecting platelet-rich plasma (PRP), an increasingly used therapy for releasing growth factors into degenerative tendon. However, high-quality randomised clinical trials on this topic are lacking. The aim of this study was to evaluate the effect of a PRP injection in patients with chronic Achilles tendinopathy. Methods In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
128
1
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(137 citation statements)
references
References 0 publications
2
128
1
6
Order By: Relevance
“…However, other studies of large series have reported that PRP treatment of tendinopathy is no more effective than placebo [44,45]. Thus, this issue remains challenging and requires further studies to clearly define the effectiveness of PRP therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies of large series have reported that PRP treatment of tendinopathy is no more effective than placebo [44,45]. Thus, this issue remains challenging and requires further studies to clearly define the effectiveness of PRP therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The potential effect of PRP on neovessels has only been studied once in Achilles tendinopathy [4,5,8,12,14,15,29,40]. It is hypothesized that the formation of neovessels is related to the release of vascular endothelial growth factor (VEGF), a potent stimulator of angiogenesis [7].…”
Section: Neovessels and Therapeutic Interventionsmentioning
confidence: 99%
“…Perhaps, preparation method of PRP, its concentration, source (e.g. auto-alloand xenogenic base) and its constitutions (platelet or platelet with buffy coat) are suggested to be different between several studies [30,[101][102][103]. As a general rule, effective PRP is prepared via two steps centrifugation with the combination of platelets and buffy coats (inflammatory cells) and has a 6 to 7 times more platelets than the circulating blood [30].…”
Section: Healing Promotive Factorsmentioning
confidence: 99%